Low-molecular-weight paramagnetic 19F contrast agents for fluorine magnetic resonance imaging - Herynek, Vít; Martinisková, Marie; Bobrova, Yulia; Gálisová, Andrea; Kotek, Jan; Hermann, Petr; Koucký, Filip; Jirák, Daniel; Hájek, Milan (Magma (New York, N.Y.), 2019)
OBJECTIVE: 19F MRI requires biocompatible and non-toxic soluble contrast agents with high fluorine content and with suitable 19F relaxation times. Probes based on a DOTP chelate with 12 magnetically equivalent fluorine atoms (DOTP-tfe) and a lanthanide(III) ion shortening the relaxation times were prepared and tested. METHODS: Complexes of DOTP-tfe with trivalent paramagnetic Ce, Dy, Ho, Tm, and Yb ions were synthetized and characterized. 19F relaxation times were determined and compared to those of the La complex and of the empty ligand. In vitro and in vivo 19F MRI was performed at 4.7 T. RESULTS: 19F relaxation times strongly depended on the chelated lanthanide(III) ion. T1 ranged from 6.5 to 287 ms, T2 from 3.9 to 124.4 ms, and T2* from 1.1 to 3.1 ms. All complexes in combination with optimized sequences provided sufficient signal in vitro under conditions mimicking experiments in vivo (concentrations 1.25 mM, 15-min scanning time). As a proof of concept, two contrast agents were injected into the rat muscle; 19F MRI in vivo confirmed the in vivo applicability of the probe. CONCLUSION: DOTP-based 19F probes showed suitable properties for in vitro and in vivo visualization and biological applications. The lanthanide(III) ions enabled us to shorten the relaxation times and to trim the probes according to the actual needs. Similar to the clinically approved Gd3+ chelates, this customized probe design ensures consistent biochemical properties and similar safety profiles.
Keywords: Molecular Weight; oxazoly; Phosphinic acid complexes; Rats; Contrast Media; ligandy; Fluorine-19 Magnetic Resonance Imaging; molekulová hmotnost; fluor; Oxazoles; pyrimidinony; kontrastní látky; chelátory; Ions; Molecular probes; Relaxation times; Fluorine-19 magnetic resonance imaging; Lanthanoid Series Elements; krysa rodu Rattus; Pyrimidinones; Magnetics; lanthanoidy; ionty; Ligands; Macrocyclic ligand complexes; zvířata; Lanthanide series elements; zobrazování fluorovou magnetickou rezonancí; magnetismus; Fluorine; Chelating Agents; Animals